PELATIHAN MICROSOFT EXCEL 2016 DI MIS AL-ISLAMIYAH BATU PUTIH DESA ALILA TIMUR, KABUPATEN ALOR-NTT - Karel L. Klakik; Isnainin Samiun; Kornelis Maata; Menase Kupeilang; Inang Aulia Rais; Jon Idrison Molina; Julminggu J. Selly (Fakultas Teknologi Informasi dan Industri Unisbank, 2026)
Digital literacy development at the primary education level is essential in response to rapid advances in information technology. One fundamental skill required is data processing using Microsoft Excel 2016. This community service activity aimed to improve the knowledge and skills of students at MIS Al-Islamiyah Batu Putih, Alila Timur Village, Alor Regency–NTT, in using Microsoft Excel 2016. The training employed lecture sessions, demonstrations, hands-on practice, discussions, and evaluations through pre-test and post-test. Training materials included an introduction to the Excel interface, simple table creation, basic formulas such as SUM and AVERAGE, and data formatting. The results indicate improvements in students’ knowledge, technical skills, and conceptual understanding of data processing. In addition, positive changes were observed in students’ attitudes, particularly increased confidence and active participation during technology-based learning activities. This program contributes to strengthening digital literacy among elementary school students and supports the development of essential computer skills for future learning.